Manajemen Perubahan: Studi atas Entering, Contracting, dan Diagnosing dalam Transformasi Organisasi - M. Irwan Nulhakim; Hari Widiyantoro, Hari Widiyantoro (CV. ITTC INDONESIA, 2025)
Change management is a systematic approach to managing organizational transformation in order to achieve efficiency, effectiveness, and competitive advantage. This study discusses the initial three stages of change management: Entering, Contracting, and Diagnosing. Entering involves the initial process of identifying problems and the urgency for change; Contracting focuses on formulating agreements between the change agent and the organizational client; while Diagnosing is carried out to analyze the root causes of problems in order to develop appropriate change strategies. Using a qualitative approach through literature review and case studies from Indonesian organizations, this article highlights the importance of these initial stages in supporting well-planned and sustainable change. The findings are expected to serve as a practical reference for organizations in designing effective organizational transformation.